Utilization of Twitter Social Media in Tourism Recovery in Yogyakarta - Suranto Suranto; Akhmad Habibullah; Arif Zainudin (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
Yogyakrta as one of the main tourism destinations in Indonesia suffered losses of up to 10 trillion and continued to grow during the pandemic. However, with the issuance of various regulations and the improvement of covid-19 handlers, several sectors have begun to resume operations with strict health protocols, including tourism. In an effort to save tourism in Yogyakarta, the government is re-promoting tourism during the pandemic, one of which is by utilizing social media twitter. Through the official account of the Tourism Office, @visiting_jogja research tries to analyze how the Yogyakarta government through its twitter account promotes tourism recovery in Yogyakarta. This research uses a qualitative method with a descriptive approach, data analysis using analytical tools in the form of the NVivo Plus 12 application, starting with data input through the Nvivo NCapture feature, then coding, exploration, data visualization and, data presentation and drawing conclusions. The results showed that the use of social media for the dissemination of tourism information in Jogja City was very effective, the dissemination of information related to tourism, events and activities as well as additional important information about the pandemic became very quickly resolved